Comparative metabolomics reveals complex metabolic shifts associated with nitrogen-induced color development in mature pepper fruit - Zhang, Lu; Zhang, Fen; He, Xuanyi; Dong, Yuehua; Sun, Kai; Liu, Shunli; Wang, Xiaozhong; Yang, Huaiyu; Zhang, Wei; Lakshmanan, Prakash; Chen, Xinping; Deng, Yan (Frontiers in Plant Science, 2024)
Pigments derived from red pepper fruits are widely used in food and cosmetics as natural colorants. Nitrogen (N) is a key nutrient affecting plant growth and metabolism; however, its regulation of color-related metabolites in pepper fruit has not been fully elucidated. This study analyzed the effects of N supply (0, 250, and 400 kg N ha-1) on the growth, fruit skin color, and targeted and non-target secondary metabolites of field-grown pepper fruits at the mature red stage. Overall, 16 carotenoids were detected, of which capsanthin, zeaxanthin, and capsorubin were the dominant ones. N application at 250 kg ha-1 dramatically increased contents of red pigment capsanthin, yellow-orange zeaxanthin and β-carotene, with optimum fruit yield. A total of 290 secondary metabolites were detected and identified. The relative content of most flavonoids and phenolic acids was decreased with increasing N supply. Correlation analysis showed that color parameters were highly correlated with N application rates, carotenoids, flavonoids, phenolic acids, lignans, and coumarins. Collectively, N promoted carotenoid biosynthesis but downregulated phenylpropanoid and flavonoid biosynthesis, which together determined the spectrum of red color expression in pepper fruit. Our results provide a better understanding of the impact of N nutrition on pepper fruit color formation and related physiology, and identification of target metabolites for enhancement of nutritional quality and consumer appeal.